2021
DOI: 10.1002/jmv.26827
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of cellular immunity function and inflammatory factors assays in alveolar lavage fluid for severe COVID‐19 pneumonia

Abstract: In this study, we aimed to investigate the changes of lymphocyte subsets (CD3 + , CD4 + , CD8 + ) and inflammatory factors , hypersensitive C-reactive protein [HS-CRP], and procalcitonin [PCT]) of alveolar lavage fluid in patients with severe corona virus-2019 (COVID-19) pneumonia and their clinical impact on the assessment of disease severity and prognosis. Twenty-four patients with severe COVID-19 pneumonia were admitted to the intensive care unit (ICU) of the Ezhou Central Hospital from February 1 to March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(73 reference statements)
0
3
1
Order By: Relevance
“…Our results are different from the results of the paper by Liao and Yang [ 1 ]. Concentrations of PCT and IL-6 were not statistically different between survivors and non-survivors, and only PCT in BALF ( p = 0.0759) and IL-6 in serum ( i = 0.0630) tended to be higher in non-survivors [ 3 ].…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are different from the results of the paper by Liao and Yang [ 1 ]. Concentrations of PCT and IL-6 were not statistically different between survivors and non-survivors, and only PCT in BALF ( p = 0.0759) and IL-6 in serum ( i = 0.0630) tended to be higher in non-survivors [ 3 ].…”
contrasting
confidence: 99%
“…The research article “Clinical Significance of Cellular Immunity and Inflammatory Factors Assays in Alveolar Lavage Fluid for Severe COVID-19 Pneumonia” by Liao and Yang [ 1 ] reported that the concentrations of interleukin-6 (IL-6), C-reactive protein (CRP), and procalcitonin (PCT) in the alveolar lavage fluid and in the serum of survivors were lower compared to those of non-survivors. Levels of IL-6, CRP, and PCT were higher in samples of alveolar lavage than in the serum, indicating that viral infections lead to abnormal oxygen and carbon dioxide exchange in the alveoli and to a secondary inflammation-mediated immune response disorder.…”
mentioning
confidence: 99%
“…The severity of the disease also correlates with cytokine levels and these patients secrete higher levels of IL-6 and IL-10 ( 175 ). Thus, in ICU patients a further increase in IL-6 and IL-10 plus TNF-α ( 165 ) has been observed and has also been found to be higher in the bronchoalveolar lavage fluid of deceased patients than in those who survive IL-6 ( 120 ). The increase in TNF-α may explain why antibody levels correlate with disease severity, since this cytokine secreted by CD4+ T cells serves as a co-stimulatory signal for B cells.…”
Section: Natural Infection With Sars-cov-2 (Covid-19)mentioning
confidence: 98%
“…In addition, symptomatic SARS-CoV-2 infection tends to elicit a higher peripheral blood T cell response with respect to asymptomatic infection (117,118).The reduced frequencies of peripheral T cells during acute infection are likely to be associated with decreased CD4+ T cell proliferation and CD8+ T cell hyperactivation with T cell migration into the lungs (119). However, Liao L. et al (120) have observed an increase of T cells in bronchoalveolar lavage fluids in mild patients but not in severe patients, suggesting a difference in T cell migration into the lungs in severe patients (120)(121)(122).…”
Section: Natural Infection With Sars-cov-2 (Covid-19)mentioning
confidence: 99%